Choice Determining Factors and Attributes of Urban Transportation by Travellers: A Case Study of the AccraTakoradi Route, in Ghana. - Etsibah, Samuel Alphonse; Agyemang, Ernest (Ghana Journal of Higher Education Management, 2023)
Several factors come to play when determining the reasons for the choice of a specific mode of transport. These may broadly be classified into characteristics such as the purpose, objective of the trip, attributes of the transport services and the socio-economic and demographic status of the traveller. The objective of this paper is to find the factors and attributes that influence the choice of transport modes. The primary data was generated from input on travellers at various transport terminals in Accra. Independent variables, such as the socio-economic and demographic factors of passengers, were tested to show how they influenced the dependent variable being choice of transport modes. The influence of other, variables such as the perceived and physical attributes of transport services were analysed. Using quantitative methods, such as surveys enabled primary data to be collected and analysed using univariate, bivariate analysis and multinomial logistic regression. The data showed that many variables and attributes influence travellers choice of transport services or mode. They included the socio-economic and demographic factors of passengers, such as income, occupation and distances from origin and destinations. The paper concludes with some policy, practical and theoretical recommendations.